2014
DOI: 10.1080/00220973.2013.876228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Genre and Content Knowledge on Historical Thinking With Academically Diverse High School Students

Abstract: Historians use a range of genres in presenting their subjects, yet educators have increasingly privileged argumentation to help novices to reason with historical content. However, the influence genre and content knowledge are relatively unmeasured in this discipline. To learn more, the authors asked 101 eleventh-grade students to compose an argument or a summary on the Gulf of Tonkin and analyzed basic and disciplinary reading and writing measures. Results indicate that students with adequate content knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
5
0
4
Order By: Relevance
“…These methods have shown that learning is affected by several kinds of interactions: The interaction between media (writing versus talk) and achievement level (Rivard, 2004); the interaction between individual traits such as level of self-monitoring and the type of writing task (Galbraith, 1996;Kieft, Rijlaarsdam, & van den Bergh, 2008); and the interaction between the writer's knowledge or achievement level, and the type of activity or instructional support (De La Paz & Wissinger, 2015;Gil, Bråten, Vidal-Abarca, & Strømsø, 2010;Hebert, Graham, Rigby-Wills & Ganson, 2014).…”
Section: Recent Progress In the Methodology Of Writing To Learnmentioning
confidence: 99%
“…These methods have shown that learning is affected by several kinds of interactions: The interaction between media (writing versus talk) and achievement level (Rivard, 2004); the interaction between individual traits such as level of self-monitoring and the type of writing task (Galbraith, 1996;Kieft, Rijlaarsdam, & van den Bergh, 2008); and the interaction between the writer's knowledge or achievement level, and the type of activity or instructional support (De La Paz & Wissinger, 2015;Gil, Bråten, Vidal-Abarca, & Strømsø, 2010;Hebert, Graham, Rigby-Wills & Ganson, 2014).…”
Section: Recent Progress In the Methodology Of Writing To Learnmentioning
confidence: 99%
“…In contrast, students often write rather linear and factual recounts and tend to use sources only as carriers of information (McCarthy Young & Leinhardt, 1998;Stoel, 2017;Wineburg, 1991). Several recent studies have shown that an explicit (discipline-based) writing instruction positively affects the ability of students to articulate historical reasoning in their writing (De La Paz & Felton, 2010;De La Paz & Wissinger, 2015;Van Drie, Braaksma, & Van Boxtel, 2015). Other research showed positive effects of instruction on referencing sources and integrating source-information in a written essay (Britt & Aglinskas, 2002;De La Paz, 2005).…”
Section: Instructional Strategies and Approachesmentioning
confidence: 99%
“…Neben den Schreibkompetenzen bzw. dem Textsortenwissen scheint auch das inhaltliche Vorwissen der Lernenden für die Wirksamkeit von Schreibinterventionen von Bedeutung zu sein (De La Paz & Wissinger, 2015;Gil et al, 2010;Hebert et al, 2014). Argumentationsorientierte Schreibaufgaben beispielsweise, die eigentlich das tiefgründige Durchdringen einer Thematik bewirken sollen (Wiley & Voss, 1999), können sich bei leistungsschwächeren Lernenden kontraproduktiv auf den Lernerfolg auswirken (De La Paz & Wissinger, 2015;Gil et al, 2010).…”
Section: Stand Der Forschungunclassified
“…dem Textsortenwissen scheint auch das inhaltliche Vorwissen der Lernenden für die Wirksamkeit von Schreibinterventionen von Bedeutung zu sein (De La Paz & Wissinger, 2015;Gil et al, 2010;Hebert et al, 2014). Argumentationsorientierte Schreibaufgaben beispielsweise, die eigentlich das tiefgründige Durchdringen einer Thematik bewirken sollen (Wiley & Voss, 1999), können sich bei leistungsschwächeren Lernenden kontraproduktiv auf den Lernerfolg auswirken (De La Paz & Wissinger, 2015;Gil et al, 2010). Um Lernende mit geringerem Vorwissen zu unterstützen, haben sich zusammenfassende Schreibaktivitäten als förderlicher erwiesen (De La Paz & Wissinger, 2015;Gil et al, 2010), insbesondere wenn das Lernziel in der Reproduktion von Wissen besteht (Hebert et al, 2013).…”
Section: Stand Der Forschungunclassified
See 1 more Smart Citation